Tyre wear nanoparticles as test for a nano risk governance framework - van Broekhuizen, Pieter; Säämänen, Arto; Schuurbiers, Daan; Isigonis, Panagiotis; Jensen, Keld A.; Kühnel, Dana; Le Blansch, Kees (Frontiers in Environmental Science, 2022)
The Horizon 2020 consortia NanoRigo, Gov4Nano and RiskGONE jointly developed a nano risk governance framework (NRGF), fit for use for the practice of nanomaterials’ development and use, understandable and executable for stakeholders involved in manufacturing, using or regulating nanomaterials, or confronted with incidental exposure to generated nanomaterials. The NRGF includes risk management models, tools and approaches relevant to nanomaterials, as well as nano-oriented LCA and grouping, and takes into account socio-economic aspects and risk-benefit assessment. Special attention was paid to operationalizing concern assessment within the framework of the risk governance approach, emphasizing the different nature of quantitative risk assessment and qualitative concern assessment. The usefulness and added value of the NRGF was tested by means of a case study on rubber tyres. This case study performed a “mock-up” risk and concern assessment of the use of manufactured nanomaterials in the rubber tyre tread and the environmental release of tyre wear particles (TWP) from this tread during car driving. With a focus on the release and hazards of nano-TWP, an approach using the NRGF methodology was defined in collaboration with a group of real-life stakeholders. Simultaneously a group of scientific experts assessed the usefulness of the available tools and methods for assessing this nano-TWP release and investigated related broader societal concerns. The exercise concludes that so far, an exclusive risk assessment of nano-TWP is a step too far, due to the lack of nano-specific health- and environmental exposure and hazard data. Moreover, it seems that public concern about nano-sized TWP emissions is still limited, contrary to emerging scientific concerns. The case study underlines the complexity of deriving robust recommendations for “real-life” cases. Many questions remain on how to weigh the available technical and social evidence in nano risk governance.